The Berenstain Bears lend a helping hand - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1998)
Mama Bear hopes to teach the cubs to think of others instead of only themselves by having them help an elderly neighbor clean out her attic.